An Action-Independent Role for Midfrontal Theta Activity Prior to Error Commission - Estiveira, João; Dias, Camila; Costa, Diana; Castelhano, João; Castelo-Branco, Miguel; Sousa, Teresa (Frontiers in Human Neuroscience, 2022)
Error-related electroencephalographic (EEG) signals have been widely studied in relation to the human cognitive capability of differentiating between erroneous and correct actions. Midfrontal error-related negativity (ERN) and theta band oscillations have been found to underlie post-action error monitoring. However, it remains elusive how early monitoring activity is trackable, and which pre-response brain mechanisms relate to performance monitoring. Moreover, it is still not clear how task-specific parameters, such as cognitive demand or motor control, influence these processes. Here, we aimed to test pre- and post-error EEG patterns for different types of motor responses and to investigate the neuronal mechanisms leading to erroneous actions. We implemented a go/no-go paradigm based on keypress and saccadic responses. Participants received an initial instruction about the direction of the response to be given based on a facial cue and a subsequent one about the type of action to be performed based on an object cue. The paradigm was tested in 20 healthy volunteers combining EEG and eye tracking. We found significant differences in reaction time, number, and type of errors between the two actions. Saccadic responses reflected a higher number of premature responses and errors compared to the keypress ones. Nevertheless, both types of erroneous actions led to similar EEG patterns, supporting previous evidence for increased ERN amplitude and midfrontal theta power during error commission. Moreover, we found pre-error decreased theta activity independent of the type of action. Source analysis suggested different origin for such pre- and post-error neuronal patterns, matching the anterior insular cortex and the anterior cingulate cortex, respectively. This opposite pattern supports previous evidence of midfrontal theta not only as a neuronal marker of error commission but also as a predictor of action performance. Midfrontal theta, mostly associated with alert mechanisms triggering behavioral adjustments, also seems to reflect pre-response attentional mechanisms independently of the action to be performed. Our findings also add to the discussion regarding how salience network nodes interact during performance monitoring by suggesting pre- and post-error patterns have different neuronal sources within this network.